Penatalaksanaan Fisioterapi Pada Kasus Cerebral Palsy Spastic Athetoid Quadriplegi Di Pediatric And Neurodevelopmental Therapy Centre (PNTC) - Ichsan, Muhammad Khairil, Umi Budi Rahayu, S.Fis., Ftr., M.Kes (2014)
Background: Cerebral palsy (CP) is any group of motor disorders that persist, non-progressive, which occurs in children at the beginning of the growth process caused by brain damage due to birth trauma or intra uterine pathology. Definition spastic nature or is characterized by spasms hypertonic, thus muscles and stiff movements, while also known as athetoid or dyskinetic movements motion not controlled, abnormal attitude, and involuntary movements or by itself, and quadriplegia that is fourth member of body motion is attacked altogether. So, athetoid CP spastic quadriplegia is uncontrolled movements which are involuntary and hipertonus on all four limbs affected. In addressing these problems with the modality used is Neuro Developmental Treatment (NDT) which includes inhibition, stimulation and facilitation. Objective: To determine the effect of exercise therapy with methods of Neuro Development Treatment (NDT) in reducing spasticity and improving motion control and balance in order to improve the functional ability of the CP spastic athetoid quadriplegia. Results: After treatment for 6 times the obtained results on the assessment of spasticity with scale Asworth: shoulder T1 = 2 to T6 = 2, elbow T1 = 2 to T6 = 2, wrist T1 = 2 to T6 = 2, hip T1 = 2 to T6 = 2, knee T1 2 to T6 = 2, and ankle T1 = 3 becomes T6 = 3. Not to change. On examination of the functional activity of the GMFM is obtained at the initial examination (T0): 40.1% and at the end of the evaluation (T6) becomes: 42.1%. From start to finish increased by 2%. Conclusion: Management of physiotherapy on condition athetoid CP spastic quadriplegia with exercise therapy using NDT methods showed no decrease spasticity with Asworth scale and showed improvement of functional ability invitation GMFM.